STUDY OF ENDOPHYTIC FUNGAL COMMUNITY FROM BARK OF VENTILAGO MADRASAPATNA GAERTN. - K.N.RAVINDRA; THOYAJAKSHA; M.NARAYANAPPA; P. SHARANAPPA (International Journal of Pharma and Bio Sciences, 2013)
Endophytic fungi were isolated from the inner bark of Ventilago madrasapatna, a well-known medicinal plant of India. It was investigated for endophytic mycoflora as a possible source of bioactive secondary metabolites. A total 66 isolates of 14 species belongs to 5 classes, were studied adopting a standard isolation protocol. The colonization frequency of the endophytic fungi was reported as 87.84%. Fungus composition included 6.25% Eurotiomycetes, 9.3% Dothideomycetes, 14.26% Soradariomycetes, 11.08% Ascomycetes, 2.6% Leotiomycetes and 1.3% isolates were classified under Mycelia sterilia. The sterile endophytic fungi presently reported are expected to add to the list of new fungal species. Among the endophytic flora, Fusarium oxysporum was found to be the core-group fungus with a colonization frequency of 34.22%.Cladosporium cladosporiodes and Botrytis sp. are present only in bark of plant collected in Belur forest region. These results indicated that distribution of endophytic fungi is mainly influenced by environment factors.